Application of Artificial Intelligence as Evidence in Indonesian Courts - I Ketut Sukewati Lanang Putra Perbawa (Universitas Pendidikan Ganesha, 2021)
Artificial Intelligence is one of the technologies that exist in the world and can resemble humans while Artificial Intelligence can do what humans actually do such as Learning, Planning, Critical Thinking, Problem Solving, and many more. Because of this, some states use it in court. Artificial Intelligence uses it as evidence to prove multiple cases and makes it easier for prosecutors, judges and lawyers to work. This study aims to examine the application of Artificial Intelligence as evidence in courts in Indonesia. This research is a literature review research. Data collection is carried out by reviewing the literature related to the application of Artificial Intelligence as evidence in courts in Indonesia. Various information was collected from various sources such as books, papyrus, articles, research reports, and so on. Various information that has been collected is then reviewed, formulated, analyzed, and outlined in writing. Data collection is done by using documentation techniques, namely by reading, reviewing, studying, and noting the essence of the literature. The results show that in Indonesia there is no law on Artificial Intelligence so it will be difficult to use it in court as evidence because according to several sources in the procedural law there are some legal evidence that can only be used in court. However, crimes that occur in Indonesia are usually related to technology, so all governments must form a law on Artificial Intelligence.